Analisis Persepsi Mahasiswa Terhadap Pelaksanaan Pembelajaran Dalam Jaringan (Daring) Mata Kuliah Praktik Fisika Terapan - Purwanto Purwanto; Arif Rakhman Suharso; Susanto (Jurnal Maritim Polimarin, 2022)
Vocational campuses are campuses where most of the learning is carried out through practice with the aim that students have more skills and competencies when working in industry. However, in the COVID-19 pandemic situation, all learning must be carried out online, both theoretical and practical courses. The purpose of this study was to determine the level of feasibility and success of the online learning of applied physics practicum courses at the Politeknik Maritim Negeri Indonesia through analysis of student perceptions with the provision that the perception index is positive if it has a percentage of >40%. The method used in this research is descriptive quantitative. The object of this research is students who take practical applied physics courses from the Nautika study program. The number of students who filled out the questionnaire was determined by using a purposive random sampling technique. The data was obtained through a googleform questionnaire and shared via whatsapp messages. The results of the study showed that the student perception index got a positive value with a feasibility percentage of 87% for the component of teaching and learning activities, 98% for the component of lecturer competence and 88% for the component of facilities and infrastructure.